Fertilization and resistance of plants to diseases and nematodes - Pípolo, Valéria Carpentieri; Assis, Joston Simão; Garcia, Ivone P. (Semina: Ciências Agrárias, 1993)
<!–[if gte mso 9]> Normal 0 21 MicrosoftInternetExplorer4 <![endif]–> <!– /* Font Definitions */ @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> The degree and level of the development of plant are typic for each combination host-pathogen-environment and, among others factors, soil fertility determines the frequency and the geographyc distribuition of the plant diseases. In addition to the genetic resistance, the plant nature is the most acceptable form of the fertilizer influence on resistance, since fertilizers are, frequentely related to the phisiologic characteristics of the plants. Most of the researchs on the effect of soil fertility on plant resistance to diseases have been conducted with N, P, K, Ca and some nutrients. The studies have shown that: a) the effect of a single nutrient on the plant resistance to disease is different of that when several nutrients are combined; b) the way by which the nutrient is supplied affects the plant resistance; c) the great variability observed in respect to the effect of a nutrient on the plant resistance to diseases permits no generalization.